Examining the effect of input factor allocation management on tangerine production: Evidence from Selayar Islands Regency, Indonesia - Abdushamad, .; Salam, Muslim; NixiaTenriawaru, A.; Jamil, Muhammad Hatta; Rukmana, Didi; Hamid, Nurdjanah; Kamarulzaman, Nitty Hirawaty; Rahmadanih, .; Heliawaty, .; Busthanul, Nurbaya; Fudjaja, Letty; Syam, Siti Hardiyanti; et al. (Elsevier, 2025)
The Indonesian economy relies on agricultural growth. Thus, the horticultural subsector must grow sustainably to maintain its economic contribution. In agriculture, input factors are crucial for increasing commodity yields. Hence, this study aimed to examine the effect of allocating input factors on tangerine production in Selayar Islands Regency. The binary logistic regression was employed to analyze primary data collected from 156 tangerine farmers, which served as the sample size, to achieve the research objective. Based on the findings, it was found that the variables of education length, farmer group membership, tangerine farming distance to the farmer's house, labor, pesticides, herbicides, urea fertilizer, manure, and NPK fertilizer all had a significant impact on tangerine production. However, the distance from farmers' houses to farms and insecticide application variables have a significantly negative effect on tangerine yields. These findings provide essential indications and valuable insights that promote and encourage the effective allocation of input factors for the commodity. The findings have led to policy recommendations aimed at enhancing the efficiency of input factor allocation. Farmers can boost their output by improving their skills in tangerine farming management, joining farmer groups, and applying more urea and NPK fertilizers and manure. Optimizing pesticide use can also increase tangerine production. Then, to remain productive, tangerine farmers must employ a combination of conventional and organic fertilizers, use pesticides sparingly, reduce the application of insecticides as well, and build a farm-house within the area of tangerine farming to shorten the distance between the farmers' house and their farms.